2008
DOI: 10.1176/foc.6.2.foc212
|View full text |Cite
|
Sign up to set email alerts
|

Adding or Switching Antipsychotic Medications in Treatment-Refractory Schizophrenia

Abstract: Objective-This study compared patients with schizophrenia whose antipsychotic medications were switched to manage treatment-resistant positive psychotic symptoms with those for whom another antipsychotic was added. Psychiatrists' characteristics and perceptions of effectiveness of the medication change on clinical outcomes were also reported.Methods-Psychiatrists participating in a nationally representative mailed survey (N=209) reported on the clinical features, management, and response to the change in antip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 34 publications
0
12
1
Order By: Relevance
“…[35,49] For example, a multicentre audit of antipsychotic drug prescribing for inpatients in the UK [17] found that the most common clinical indication for the use of polypharmacy was the perceived failure of a single antipsychotic to control symptoms. However, this finding is somewhat at odds with the observation by Kreyenbuhl et al [42] that psychiatrists do not recognize antipsychotic polypharmacy as particularly effective in reducing psychotic symptoms or improving overall functioning. Nevertheless, to treat a poorly responsive schizophrenic illness, many psychiatrists would choose to combine two antipsychotics rather than proceed to a trial of clozapine.…”
Section: Risks Of Antipsychotic Polypharmacymentioning
confidence: 78%
See 1 more Smart Citation
“…[35,49] For example, a multicentre audit of antipsychotic drug prescribing for inpatients in the UK [17] found that the most common clinical indication for the use of polypharmacy was the perceived failure of a single antipsychotic to control symptoms. However, this finding is somewhat at odds with the observation by Kreyenbuhl et al [42] that psychiatrists do not recognize antipsychotic polypharmacy as particularly effective in reducing psychotic symptoms or improving overall functioning. Nevertheless, to treat a poorly responsive schizophrenic illness, many psychiatrists would choose to combine two antipsychotics rather than proceed to a trial of clozapine.…”
Section: Risks Of Antipsychotic Polypharmacymentioning
confidence: 78%
“…Clinicians tend to switch more often than they add another antipsychotic. [42,43] But not uncommonly, if a patient's mental state improves during such a switch, the prescribing clinician may be disinclined to complete the switch because of a perceived risk of destabilizing the illness, again potentially leading to continuing antipsychotic polypharmacy. [44][45][46] In the UK, oral antipsychotic medication is co-prescribed to around half of patients receiving depot/long-acting injection preparations; [47,48] in a proportion of cases the oral antipsychotic is the same drug as the depot, a situation that would not be considered as use of combined antipsychotics, although this practice is still a major contributor to high antipsychotic dosage.…”
Section: Risks Of Antipsychotic Polypharmacymentioning
confidence: 99%
“…In practice, clinicians appear to perceive antipsychotic polypharmacy to be ineffective for persistent, treatmentresistant positive psychotic symptoms. 13 The combination of typical and atypical antipsychotics seems to produce a typical response (i.e. high rates of movement disorder).…”
Section: Editorialmentioning
confidence: 99%
“…As there was no effect of age/experience of prescribers on the choice of prescription, it can be speculated that prescription habits may get inherited from the senior clinicians. In a similar survey done in the US, it was found out that psychiatrists who added rather than switched antipsychotics reported more frequent attendance at educational programmes sponsored by pharmaceutical companies [19]. There was no evidence of influence of pharmaceutical industry on the choice of treatment in this sample.…”
Section: Discussionmentioning
confidence: 61%
“…In a similar survey carried out in the US, looking into only treatment-resistant cases, 33% of cases were on combination therapy comparing to 46.1% in this sample [19]. Although the frequency of antipsychotic polypharmacy was found to vary according to patient, illness, setting and provider variables, rates in schizophrenia commonly were reported to range from 7% to 50% [13,20].…”
Section: Discussionmentioning
confidence: 67%